The Effect Of Job Boredom, Cyberloafing, And Perceived Organizational Justice On Employee Performance Of Generation Z, With Mediating Role Of Organizational Commitment, In The Indonesia Logistics Sector - Dedianto Turnip; Bahtiar Usman; Deasy Aseanty (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This quantitative research aims to examine the influence of job boredom, cyberloafing, and perceived organizational justice on employee performance of generation Z, with mediating role of organizational commitment, in the logistics sector of warehousing and land transportation in Indonesia. The cross-sectional approach was used in data collection by distributing questionnaires to employees working in 8 logistics companies in Jakarta during October until November 2024, with 391 respondents involved. Data analysis is using Structural Equation Modelling with software AMOS version 23. The results of the hypothesis test show there is negative effect of job boredom and positive effect of perceived organizational justice on employee performance, and there is mediating role of organizational commitment. However, cyberloafing does not affect employee performance and organizational commitment. Companies need to strive on increasing organizational commitment to mitigating the negative impact of job boredom and increase the positive influence of perceived organizational justice on employee performance.